Implementasi Program Jaminan Kesehatan Medan Berkah (JKMB) pada Pengemis di Kota Medan - Cicilia Kimberly Oldy Saragih; Fajar Utama Ritonga (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Equal access to health services is a fundamental right of citizens. However, vulnerable groups such as beggars are often neglected because they do not have valid residence documents. The Medan City Government launched the Medan Berkah Health Insurance Program (JKMB) to support universal Health Coverage, allowing free health services only with a Medan ID card. This study aims to assess the implementation of JKMB on beggars in Medan City by using the implementation suitability model from David C. Korten, which emphasizes the relationship between programs, organizations, and beneficiaries. The method used is a descriptive qualitative approach, with data collection through in-depth interviews, observations, and documentation studies. Informants consisted of beggars without identity who had been disciplined by Social Services, program Implementation officers, and academics in the field of social welfare. The results showed that JKMB can only be accessed by beggars while under the supervision of Social Services, through temporary identities such as "Mr. X". After being repatriated (reunification), access to health services cannot be continued due to the absence of An ID. The Program has not been able to reach marginalized groups on an ongoing basis, and there has been no integration of cross-sector data systems. The findings expose the discrepancy between program design and Target conditions, highlighting the importance of more inclusive policy reformulation, facilitation of identity ownership, and inter-agency coordination to create equitable and sustainable health access for all citizens